(untitled) (Fiep Bulletin - online, 2014)
The pressure ulcer (PU) is a lesion on skin and underlying tissues, caused by a lack of blood supply due to the continuous pressure in a certain area. The PU is caused by a combination of factors, being located internally or externally to the patient, but even if the individual is exposed to external factors, the human body does not automatically develops PU, as the determining factor comes from the patient himself In addition, there are predisposing conditions for the occurrence of PU. This study was designed to conduct a literature review on the risk factors for pressure ulcers in the LILACS database, between 1999 and 2004. So, a research was developed in scientific articles papers until until october/2007, using as descriptors: “pressure ulcer” and “risk factors”. The main internal factors found were skin changes, advanced age, edema, marrow injury situation, changes in sensitivity and motricity, flictema in bone prominence region, and patient dependence. Among the external factors, are highlighted shear, friction, poor hygiene, inadequate mattress, rugosity in bed linen or pajamas. The conditions predisposing we most found were anemia, depression, personality disorders, anxiety, low weight, use of sedatives. This work is important to investigate the influence of the multiplicity of factors and conditions that increase the risk for PU, with a view to contributing to the prevention and reduction of complication.